Resident Stereotype, Tourist Stereotype And Attitude Toward Tourism In Pakistan: Moderating Role Of Perceived Value And Tourist-Residents Relationship - Dr. Rana Muhammad Shahid Yaqub (Corresponding Author) , Dr. Atteeq ur Rahman , Dr. Bilal Ijaz , Muhammad Murad , Muhammad Zubair Saeed (Migration Letters, 2024)
Tourism is one of the biggest industries in the world which is getting more importance in recent days due to globalization. Scholars believe that the hospitality of the local community, the residents is a big factor in promoting tourism at a certain tourist destination. However, hospitality is not the only factor there are several stereotypes associated with tourists and residents that become a challenge for tourism promotion of a certain tourist destination. The purpose of this study is to investigate the association of tourists’ and residents’ stereotypes with their attitude towards tourism. We conducted a survey to empirically test our hypothesized model wherein 317 respondents who were foreign travelers to Pakistan participated in the survey. Results of the study reveal that tourists’ and residents’ stereotypes are positively associated with their attitude towards touris[1]m through cultural acceptance while perceived value was found as a moderator in our model. This research is noteworthy because it tackles the issues and gaps in the body of knowledge in the tourism area. The focus of the research is to add relevant information to the body of literature in tourism by addressing questions about the function of tourist stereotypes, resident stereotypes, and attitudes toward tourism. The findings are beneficial to the policy makers, the tourists, and the residents for promoting tourism by reducing stereotypes.